Effect of two solanaceous plants on developmental and population parameters of the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Pereyra, Patricia Cecilia (2006)
Tuta absoluta (Meyrick) is an important tomato pest that also feeds on other host-plants from the Solanceae family. We studied the effect of two cultivated plants, tomato (Lycopersicum esculentum Mill.) and potato Solanum tuberosum L. on the development and populational parameters of T. absoluta related with host-plant suitability. Larval developmental time, pupal weight, mean fecundity and an index of host-plant quality (IPQ = pupal weight / frass weight) were estimated. Ages-pecific survivorship and fecundity life tables were constructed in the laboratory to evaluate the following populational parameters: net reproductive rate (Ro), intrinsic rate of increase (r) and generation time (T). Larval developmental time was shorter and pupal weight was higher (P < 0.0001) for larvae reared on tomato (P < 0.0001). Mean fecundity was not significantly different on both plants (P = 0.07) and food quality of host-plant was higher for tomato (P = 0.02). Mean population parameters on tomato were: Ro = 48.92; T = 27.98, r = 0.14; and on potato: Ro = 14.43; T = 32.35, r = 0.08. Although results showed that tomato was a more suitable host-plant and had a better nutritional quality than potato, when T. absoluta fed on potato the potential population increase requires attention. Under appropriate climatic conditions, spatial and temporal coincidence between crop and pest, T. absoluta could become a pest for the potato crop.